Comparative transcriptomic and proteomic signature of lung alveolar macrophages reveals the integrin CD11b as a regulatory hub during pneumococcal pneumonia infection - Zec, Kristina; Thiebes, Stephanie; Bottek, Jenny; Siemes, Devon; Spangenberg, Philippa; Trieu, Duc Viet; Kirstein, Nils; Subramaniam, Nirojah; Christ, Robin; Klein, Diana; Jendrossek, Verena; Loose, Maria; et al. (Frontiers in Immunology, 2023)
Streptococcus pneumoniae is one of the main causes of community-acquired infections in the lung alveolus in children and the elderly. Alveolar macrophages (AM) patrol alveoli in homeostasis and under infectious conditions. However, the molecular adaptations of AM upon 2 infections with Streptococcus pneumoniae are incompletely resolved. We used a comparative transcriptomic and proteomic approach to provide novel insights into the cellular mechanism that change the molecular signature of AM during lung infections. Using a tandem mass spectrometry approach of murine cell-sorted AM, we revealed significant proteomic changes upon lung infection with Streptococcus pneumoniae. AM showed a strong neutrophilassociated proteomic signature, such as expression of CD11b, MPO, neutrophil gelatinases and elastases, which was associated with phagocytosis of recruited neutrophils. Transcriptomic analysis indicated intrinsic expression of CD11b by AM. Moreover, comparative transcriptomic and proteomic profiling identified CD11b as the central molecular hub in AM, which influenced neutrophil recruitment, activation, and migration. In conclusion, our study provides novel insights into the intrinsic molecular adaptations of AM upon lung infection with Streptococcus pneumoniae and reveals profound alterations critical for the effective antimicrobial immunity.